Revisiting the finance-growth nexus in sub-Saharan Africa: Does the level of income inequality matter? - Nicholas M. Odhiambo (Research in Globalization, 2023)
In this paper, the modulating effect of income inequality in the finance-growth nexus using data from 29 sub-Saharan African (SSA) countries is examined. The study examines i) whether financial development still spurs economic growth in the studied countries, and ii) whether income inequality modulates the effect of financial development on economic growth. Three proxies of financial development and four income inequality indicators are used. The financial development indicators used include the financial development index, financial institutions index, and financial markets index, while income inequality is measured by the Palma ratio, the Gini coefficient, the Atkinson index, as well as the composite inequality (Comp) derived from the principal component analysis (PCA). The Generalised Method of Moments (GMM) has been used to examine this linkage. The study found that, on the whole, the beneficial effect of financial sector development on economic growth in the studied countries is weak, at best. This finding has been corroborated by the results of the interaction models, which show that income inequality interacts with financial development to yield a net negative effect on economic growth in four specifications, but a net positive effect in only two specifications. This finding is not surprising given the high level of income inequality that is currently ravaging some of the SSA countries. Policy implications are discussed.
Keywords: 330; Financial development; Growth; Income inequality; SSA countries